Interaction Between FIP200 and ATG16L1 Distinguishes ULK1 Complex-Dependent and -Independent Autophagy - Gammoh, Noor (2012)
Autophagy is a finely orchestrated cellular catabolic process that requires multiple autophagy-related gene products (ATG). The ULK1 complex functions to integrate upstream signals to downstream ATG proteins through an unknown mechanism. Here, we identified an interaction between mammalian FIP200 and ATG16L1, essential components of the ULK1 and ATG5 complexes, respectively. Further analyses demonstrate that this is a direct interaction mediated by a short domain of ATG16L1 which we term the FIP200-Binding Domain (FBD). The FBD is not required for ATG16L1 self-dimerization or interaction with ATG5. Importantly, FBD-deleted ATG16L1 mutant is defective in mediating amino acid starvation-induced autophagy, which requires the ULK1 complex. Intriguingly, this mutant retains its function in supporting glucose deprivation-induced autophagy, a ULK1 complex-independent process. Our study has therefore identified a novel interaction between the ULK1 and ATG5 complexes that can distinguish ULK1-dependent and -independent autophagy processes.